ANALISIS EFEKTIVITAS PENGELOLAAN ZAKAT DIGITAL GUNA MENGURANGI KEMISKINAN MENURUT PERSPEKTIF EKONOMI SYARIAH - Juriati, Juriati; Maya, Maya (PILAR, 2024)
The problem faced by the Indonesian people is inequality in income distribution or poverty. Overcoming the problem of poverty requires a comprehensive study so that it can be used as a reference in the community's social welfare program. The research method in this article uses the library study method (library research), which is a method of collecting data by understanding and studying theories from various literatures related to the research. The data analysis techniques used in this article are data reduction, data presentation and conclusion drawing in order to draw a credible final conclusion. Law Number 23 of 2011 states that the purpose of organizing zakat is to increase the efficiency and effectiveness of organizing zakat and increase the benefits of zakat, in order to achieve community welfare and alleviate poverty. The flow of technological progress determines the current state of humanity, and humans will also follow it, one of which is in the zakat institution that has used digital. Islamic economics supports the concept of digital zakat as an innovative step to optimize the collection of zakat distribution and also be able to reduce poverty.